2017
DOI: 10.1615/intjmedmushrooms.2017024492
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antitumoral Activity of Exobiopolymers from the Royal Sun Culinary-Medicinal Mushroom Agaricus brasiliensis (Agaricomycetes)

Abstract: We studied antitumor activity in vitro and in vivo and partial chemical characterization of exobiopolymers (EBPs) of Agaricus brasiliensis produced by submerged cultivation. The EBPs comprised 61.2% total sugar and 22.3% total protein, and the chromatographic profile mainly identified mannose (65.5%), galactose (17.5%), and glucose (13.1%). In vitro analysis revealed a dose with antitumor effectiveness, time-dependent treatment, and 46% inhibition of solid Walker 256 tumors in rats. Metabolic changes were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The mechanism was immunomodulatory, as shown by increased IL-12 levels, and the growth inhibition of tumor cells by the induction of apoptosis. Recently, Sovrani et al [53] reported that AbM exobiopolymers inhibited solid Walker 256 tumors in rats due to increased nitric oxide (NO -) production by peritoneal MΦ.…”
Section: Antitumor Effects Of Abm-preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism was immunomodulatory, as shown by increased IL-12 levels, and the growth inhibition of tumor cells by the induction of apoptosis. Recently, Sovrani et al [53] reported that AbM exobiopolymers inhibited solid Walker 256 tumors in rats due to increased nitric oxide (NO -) production by peritoneal MΦ.…”
Section: Antitumor Effects Of Abm-preclinical Studiesmentioning
confidence: 99%
“…In summary, the mechanisms for the AbM-induced antitumor effects in rodent models were the following: inhibition of tumor neovascularization [35,36,47,49], antimutagenesis [37], modulation of metalloproteinase and a metastatic suppressor [48], Th1 immune cell migration to tumor [45], apoptosis [7,16,49,52], and increased NOproduction by MΦ [53].…”
Section: Antitumor Effects Of Abm-preclinical Studiesmentioning
confidence: 99%